Kerajaan Allah dalam Kisah para Rasul - Richard Majefat; Sasa Wahyuti; Jessica Putri Mannuela; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the concept of the Kingdom of God in the book of Acts as a spiritual and eternal reality that transcends political power and geographical boundaries. Through the life and teachings of Jesus Christ and the work of the apostles led by the Holy Spirit, the Kingdom of God manifests and grows within the early Christian community. Using a qualitative approach through library research, this study examines how the Kingdom of God was understood, practiced, and proclaimed by the apostles, as well as its relevance for contemporary Christian life. The findings indicate that the Kingdom of God is a call to live in love, justice, and peace, with the Holy Spirit as the central force in gospel proclamation and the formation of a Christ-centered community.